2023
DOI: 10.1007/s11356-023-27472-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing environmental sustainability pathways in G7 economies: the role of energy transition, technological innovation, and demographic mobility

Abstract: Global warming remains the most devastating environmental issue embattling the global economies, with significant contributions emanating from CO 2 emissions. The continued rise in the level of greenhouse gas (GHG) emissions serves as a compelling force which constitutes the core of discussion at the recent COP26 prompting nations to commit to the net-zero emission target. The current research presents the first empirical investigation on the roles of technological advancement, demograph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…In the same vein, Akram et al [ 30 ], confirmed our findings for G7 countries and claimed that ECI, as a technological approach, contributes to curbing CDE. Moreover, Ibrahim et al [ 89 ], stated that ECI is the pathway to the neutralization of CDE and environmental sustainability in G7 economies. In the OECD context, Bigerna et al [ 90 ], highlighted the importance of ECI as the primary inhibitor factor for CDE.…”
Section: Resultsmentioning
confidence: 99%
“…In the same vein, Akram et al [ 30 ], confirmed our findings for G7 countries and claimed that ECI, as a technological approach, contributes to curbing CDE. Moreover, Ibrahim et al [ 89 ], stated that ECI is the pathway to the neutralization of CDE and environmental sustainability in G7 economies. In the OECD context, Bigerna et al [ 90 ], highlighted the importance of ECI as the primary inhibitor factor for CDE.…”
Section: Resultsmentioning
confidence: 99%
“…It was found in [5] that in the process of global economic development, emerging economies such as China and India have been driving the world's energy demand upwards. Scholars have begun to incorporate an increasing number of factors into their considerations, utilizing past data to explore the relationship between energy transition and economic growth [27,28], the application of new energy sources, and other elements influencing regional economic development [22,29,30]. Furthermore, factors such as foreign direct investment (FDI), domestic trade, domestic financial development, and the growth of the digital economy have varying degrees of influence on a country's energy transition and emissions [8,17,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Luo et al (2020) found that the establishment of major grain-producing areas was conducive to reducing agricultural carbon emissions [30]. Using the data of G7 countries, Ibrahim et al (2023) found that economic growth would intensify carbon emissions [31].…”
Section: Introductionmentioning
confidence: 99%